La mente e il corpo nella schizofrenia - Fargnoli, Domenico (Il sogno della farfalla, 2016)
Starting from the etymology of the term “mind”, the Author analyses the question mind-body involved in the history of human thought since pre-socratic philosophers. In particular, the question still stands unresolved, both from an ontological and a methodological point of view, within the “philosophy of the mind”, neurosciences and psychiatry. Moreover, in the article, the Author analyses the implications of the concept of “causation” when it is used in its deterministic and simplistic meaning to understand human beings’ behaviour, which makes one fall into mistaken interpretations and tautologies again. The Author suggests a new way to face the question in the light of Human Birth Theory by Massimo Fagioli so as to escape from the traditional opposition between the mind and the body.